Additive Effect of Spinal Cord Volume, Diffuse and Focal Cord Pathology on Disability in Multiple Sclerosis - Andelova, Michaela; Uher, Tomas; Krasensky, Jan; Sobisek, Lukas; Kusova, Eliska; Srpova, Barbora; Vodehnalova, Karolina; Friedova, Lucie; Motyl, Jiri; Preiningerova, Jana Lizrova; Kubala Havrdova, Eva; Horakova, Dana; et al. (Frontiers in Neurology, 2019)
Introduction: Spinal cord (SC) pathology is strongly associated with disability in multiple sclerosis (MS). We aimed to evaluate the association between focal and diffuse SC abnormalities and spinal cord volume and to assess their contribution to physical disability in MS patients. Methods: This large sample-size cross-sectional study investigated 1,249 patients with heterogeneous MS phenotypes. Upper cervical-cord cross-sectional area (MUCCA) was calculated on an axial 3D-T2w-FatSat sequence acquired at 3T using a novel semiautomatic edge-finding tool. SC images were scored for the presence of sharply demarcated hyperintense areas (focal lesions) and homogenously increased signal intensity (diffuse changes). Patients were dichotomized according EDSS in groups with mild (EDSS up to 3.0) and moderate (EDSS ≥ 3.5) physical disability. Analysis of covariance was used to identify factors associated with dichotomized MUCCA. In binary logistic regression, the SC imaging parameters were entered in blocks to assess their individual contribution to risk of moderate disability. In order to assess the risk of combined SC damage in terms of atrophy and lesional pathology on disability, secondary analysis was carried out where patients were divided into four categories (SC phenotypes) according to median dichotomized MUCCA and presence/absence of focal and/or diffuse changes. Results: MUCCA was strongly associated with total intracranial volume, followed by presence of diffuse SC pathology and disease duration. Compared to the reference group (normally appearing SC, MUCCA>median), patients with the most severe SC changes (SC affected with focal and/or diffuse lesions, MUCCA<median) had an almost 5-times higher risk of having moderate disability (OR 4.75, 95% CI 3.07-7.49, p<.001). Patients with normally appearing SC and MUCCA below the median had a 2-fold increased risk of being in the moderate disability group when compared to the reference patients (OR 2.15, 95% CI 1.26-3.67, p<.001). In contrast, patients with MUCCA above the median with SC lesions/diffuse changes did not differ significantly from the reference group. Conclusion: Low cervical SC volume is a strong independent predictor of physical disability in MS patients. The contribution of focal SC lesions and diffuse changes to the worse disability outcomes is limited, and present especially in patients with low SC volume.